A Smartphone App for Individual Xylazine/Ketamine Calculation Decreased Anesthesia-Related Mortality in Mice - Jara, Carlos Poblete; Carraro, Rodrigo S.; Zanesco, Ariane; Andrade, Beatriz; Moreira, Karina; Nogueira, Guilherme; Souza, Bruno L.; Prado, Thais Paulino; Póvoa, Valeria; Velander, William; Velloso, Licio A.; Araújo, Eliana P. (Frontiers in Veterinary Science, 2021)
Currently, experimental animals are widely used in biological and medical research. However, the scientific community has raised several bioethical concerns, such as the number of animals required to achieve reproducible and statistically relevant results. These concerns involve aspects related to pain, discomfort, and unwanted animal loss. Retrospectively, we compare two different approaches for anesthesia dosage: a mobile app for dose calculation and a standard dose calculation. A total of 939 C57BL/6J and Swiss mice were analyzed. We collected data on intraoperative and anesthesia-related mortality as described in electronic or physical handwritten records. Our results showed that the mobile app approach significantly reduces anesthetic-related deaths upon using doses of ketamine and xylazine. The results suggest that anesthesia-related mortality can be minimized even more using information technology approaches, helping to solve an old but transversal challenge for researchers working with experimental mice. The mobile app is a free and open code which could be implemented worldwide as an essential requirement for all anesthetic procedures in mice using xylazine and ketamine combination. As an open code app, the Labinsane initiative could also represent the starting point to unify and validate other anesthetic procedures in different species and strains.